Sea Level Variability and Change - Ivan D. Haigh (Frontiers Research Topics, 2017)
In June 2015 we held a workshop on the beautiful island of Mallorca, Spain with a focus on sea level variability and change. Over 120 sea level experts from around the world attended this workshop, from a range of different disciplines. The main aims of the workshop were to: 1.) Evaluate the current state-of-knowledge of sea level science; 2.) Identify gaps and unresolved questions in any aspect of sea level science; and 3.) Design future research to address these issue. All aspects of sea level changes were covered, from global to regional, observations and modelling, processes driving mean sea level changes and extremes, from the geological scale to the instrumental era and future projections and including impacts on the coastal zones. This E-Book presents papers that came out of that workshop. Overall, these papers illustrate the multi-disciplinary nature of sea level research, cross-cutting many fields of research including: oceanography, meteorology, geology, coastal morphodynamics, engineering and the social-economic aspects. Collectively, theses articles represent an interesting range of perspectives and original studies that contribute to understanding the dynamic nature of sea level and its impacts across a wide range of time and space scales. Enjoy reading them!